Relational Incentives Theory - Jana Gallus; Joseph Reiff; Emir Kamenica; Alan Page Fiske (Psychological Review, 2021)
Our life is built around coordinating efforts with others. This usually involves incentivizing others to do things, and sustaining our relationship with them. Using the wrong incentives backfires: it lowers effort and tarnishes our relationships. But what constitutes a `wrong' incentive? And can incentives be used to shape relationships in a desired manner? To address these and other questions, we introduce relational incentives theory, which distinguishes between two aspects of incentives: schemes (how the incentive is used) and means (what is used as an incentive). Prior research has focused on means (e.g., monetary vs. non-monetary incentives). Our theory highlights the importance of schemes, with a focus on how they interact with social relationships. It posits that the efficacy of incentives depends largely on whether the scheme fits the relational structure of the persons involved in the activity: participation incentive schemes for communal sharing relations, hierarchy for authority ranking relations, balancing for equality matching relations, and proportional incentive schemes for market pricing relations. We show that these four schemes comprise some of the most prevalent variants of incentives. We then discuss the antecedents and consequences of the use of congruent and incongruent incentive schemes. We argue that congruent incentives can reinforce the relationship. Incongruent incentives disrupt relational motives, which undermines the coordinating relationship and reduces effort. But, importantly, incongruent incentives can also be used intentionally to shift to a new relational model. The theory thus contributes to research on relational models by showing how people constitute and modulate relationships. It adds to the incentives and contracting literatures by offering a framework for analyzing the structural congruence between incentives and relationships, yielding predictions about the effects of incentives across different organizational and individual-level contexts.
Keywords: 330; incentives; social relationships; relational models; congruence; incentive schemes